Hydrophysical and Hydrochemical Controls of Cyanobacterial Blooms in Coursey Pond, Delaware (USA). Issue 1 (1st January 2019) - Andres, A. Scott; Main, Christopher R.; Pettay, D. Tye; Ullman, William J.
Abstract : Noxious cyanobacterial blooms are common in many ponds in the mid‐Atlantic Coastal Plain. In Delaware, blooms normally occur between July and October, yet no in‐depth analyses of the causes and predictors exist. A study using commercially available, high‐frequency, continuous, and automated biogeochemical sensors at Coursey Pond, Delaware, a pond known for perennial summer blooms, was conducted to investigate how hydrophysical and hydrochemical conditions affect bloom dynamics. Cyanobacterial abundance (based on the in vivo phycocyanin fluorescence and phycocyanin/chlorophyll fluorescence ratios) increases during periods of high water temperatures (up to 32°C), low discharge through the pond (mean hydraulic residence time ≥5 d) with evaporative concentration of dissolved solids, and decreasing NO3 − concentrations (reaching <0.1 mg L −1, the detection limit). These conditions lead to the uptake and depletion of bioavailable N in the pond surface waters and provide a competitive advantage for temperature‐tolerant and N‐fixing cyanobacteria. Irrigation water use within the watershed can exceed pond discharge during drier summer months, enhancing bloom‐forming conditions. Bloom intensity varies due to storms but persists until mid‐October to mid‐November when temperatures cool, daylength decreases, and discharge and NO3 − concentration recovers. Changes in these easily monitored physical and chemical parameters can serve to anticipate the onset, intensity, persistence, and the eventual dissipation of cyanobacterial blooms at Coursey Pond and similar ponds elsewhere. Therefore, the use of sensors and high‐frequency data has the potential to assist in forecasting and management of blooms. Core Ideas: Cyanobacteria blooms are common in small flow‐through ponds in the mid‐Atlantic Coastal Plain. Available biogeochemical sensors can characterize bloom onset, intensity, and dissipation. Residence time, temperature, and NO3 − concentration are robust predictors of bloom intensity. Storms temporarily disrupt blooms by flushing, but blooms reestablish once stormflow ceases. Irrigation within the watershed increases pond residence time, thus promoting blooms.